Effects of dietary glucose and starch levels on the growth, haematological indices and hepatic hexokinase and glucokinase mRNA expression of juvenile mirror carp (Cyprinus carpio). (15th February 2015) - Li, J.N.; Xu, Q.Y.; Wang, C.A.; Wang, L.S.; Zhao, Z.G.; Luo, L.
Abstract: The effect of the different dietary carbohydrate types and levels on growth performance, haematological indices and hepatic hexokinase (HK) and glucokinase (GK) genes expression involved in control of glucose metabolism, was studied in juvenile mirror carp ( Cyprinus carpio ). Two carbohydrates (glucose and starch) diets with two levels (250 and 500 g kg −1 ) were fed to triplicate groups of 35 fish for 60 days. The best weight gain rate and specific growth rate were observed in fish fed with 250 g kg −1 glucose diet and 500 g kg −1 starch diet ( P < 0.05). Fish fed with 500 g kg −1 glucose showed low feed utilization, with the highest food conversion ratio and the lowest protein efficiency ratio ( P < 0.05). Hepatosomatic index was significantly higher in fish fed with glucose diets and the 500 g kg −1 starch diet compared to 250 g kg −1 starch. CHOL, HDL‐C and LDL‐C were significantly highest in fish fed with 500 g kg −1 starch than all other diets ( P < 0.05). Hepatic GK mRNA expression level and activity were positively related to glucose and starch levels ( P < 0.05). Correlation analysis showed that hepatic glycogen concentration was increased by dietary carbohydrate content ( P < 0.05). These results suggest that GK may play a major role in the postprandial glucose utilization in juvenile mirror carp.